Petroglyphs as 'contraptions' – animacy and vitalist technologies in a Bronze Age archipelago. (3rd April 2019) - Fahlander, Fredrik
ABSTRACT: The text discusses the possibilities of Bronze Age petroglyphs working as vitalist contraptions produced to harvest or affect certain animacies in coastal milieus. As primarily magical devices, a wider range of properties of the petroglyphs becomes important besides their figurative and representational facets. For example, the mediality and physicality of the motifs, including aspects of size, embellishment, and symmetry, as well as relations between the motifs, the rock and the water. A case study based on the dense concentration of rock art in the Boglösa area of central eastern Sweden suggests, considering these aspects in full, that the petroglyphs are most likely to have worked as magic contraptions. Cut into the bedrock at the water's edge, they utilize the resilience of rock for permanence while either being consecrated by water or employed as contraptions to affect a particular body of water.